MYC expression and translocation analyses in low‐grade and transformed follicular lymphoma. Issue 6 (17th October 2017) - Aukema, Sietse M; van Pel, Roel; Nagel, Inga; Bens, Susanne; Siebert, Reiner; Rosati, Stefano; van den Berg, Eva; Bosga‐Bouwer, Anneke G; Kibbelaar, Robby E; Hoogendoorn, Mels; van Imhoff, Gustaaf W; Kluin‐Nelemans, Hanneke C; et al.
Abstract : Aims: Low‐grade follicular lymphoma (FL) (grade 1/2, FL1/2) has an annual risk of transformation of ≈3%, which is associated with aberrations in CDKN2A / B, TP53, and MYC . As in diffuse large B‐cell lymphoma, high MYC expression in transformed FL (tFL) might predict a MYC breakpoint. Methods and results: We quantified MYC expression by immunohistochemistry and digital analysis in 41 paired biopsies from 20 patients with FL1/2 with subsequent transformation and in four isolated biopsies of tFL. As controls, 28 biopsies of FL1/2 without transformation (median follow‐up of 105 months) and nine biopsies of FL3A/B were analysed. In the 20 FL1/2–tFL pairs, MYC expression was significantly higher in tFL than in the initial FL1/2 biopsies (median 54% versus 6%; 7% in FL3A, and 35% in FL3B). MYC breaks ( MYC ‐R) were detected in eight of 21 (38%) tFLs analysed by fluorescence in‐situ hybridization (FISH), with a median MYC score of 86%. In two of the analysed tFL cases, the translocation was already detected in antecedent FL1/2. MYC partners were immunoglobulin (IG) loci in three of eight cases (one IGL, one IGH, and one IGK) and non‐IG in five of eight cases (two PAX5, one BCL6, and two unknown). Of the eight MYC ‐R+ cases, six were BCL2 +/ MYC + double‐hit, one was BCL2 +/ BCL6 +/ MYC + triple‐hit, and one was MYC + single‐hit. All three IG ‐ MYC + cases showed a MYC expression level of >85%, whereas the five cases with a non‐IG MYC partner had a wider range of expression (median 68%, range 13–86%). Among the 13 MYC ‐R− tFLs, two groups with almost dichotomous MYC expression could be observed (three cases showed ≥90% MYC expression), suggesting alternative mechanisms of MYC activation. Conclusions: we show an increase in MYC expression from FL1/2 to tFL. MYC breakpoints were present in ≈40% of the cases, which is markedly higher than in de novo DLBCL. MYC expression was uniformly high in cases with an IG‐ MYC translocation but much more heterogeneous and in part independent of the presence of a MYC break in non‐IG‐ MYC and MYC ‐negative cases.